The Influence of Influencer Marketing and Social Media Marketing on Purchase Decisions with Brand Awareness as an Intervening Variable for TikTok Shop in Generation Z - Arlana Hidayatullah, Aidil; Fadhilah, Muinah; Tria Hatmanti Hutami, Lusia (Dinasti Publisher, 2025)
This study examines the effect of influencer and social media marketing on purchase decisions among Generation Z, mediated by brand awareness, within the TikTok Shop platform. The study addresses the digital marketing shift, where social media is crucial in increasing brand engagement and consumer purchasing behavior. Using quantitative methods, data were collected from 112 Generation Z consumers in Yogyakarta who had experience shopping at TikTok Shop. The analysis employed the PLS-SEM method using SmartPLS 3.0. Results indicate that while social media marketing significantly influences brand awareness and purchase decisions, influencer marketing only positively impacts brand awareness. Furthermore, brand awareness mediated the relationship between social media marketing and purchase decisions but not between influencer marketing and purchase decisions. This highlights the critical role of social media marketing over influencer marketing in driving consumer purchasing decisions on TikTok Shop, especially through brand awareness. The findings suggest marketers should prioritize strategies that enhance social media engagement to strengthen brand presence and drive consumer decisions